2011
DOI: 10.5005/jp-journals-10001-1069
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated Radiotherapy in the Treatment of Early Glottic Carcinoma

Abstract: Introduction: Given the high probability of cure, the aims of treatment are cure, laryngeal preservation and good voice quality while making effective use of available resources. In this study we analyze locoregional control (LRC) and survival following hypofractionated radiotherapy in early stage glottic squamous cell carcinoma treated at patients with early glottic squamous cell carcinoma were treated with hypofractionated radiotherapy. All patients were included in the study (M: 94%; F:6%). Median age was 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…11,35 In published reports number of patients treated with hypofractionated RT was limited and authors suggested a need for further research. 10,12,18,35 The group with hypofractionated RT reported in this paper is one of the largest published so far. More rigorous prospective studies could be considered to compare fractionation and timing of RT in the larynx and other head and neck patients and to provide stronger evidence, but published results quite consistently demonstrate that RT using fraction dose of 2.25-2.5 Gy delivered 5 days per week up to a total dose of 52-65 Gy gives the same or even better locoregional control than standard RT.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…11,35 In published reports number of patients treated with hypofractionated RT was limited and authors suggested a need for further research. 10,12,18,35 The group with hypofractionated RT reported in this paper is one of the largest published so far. More rigorous prospective studies could be considered to compare fractionation and timing of RT in the larynx and other head and neck patients and to provide stronger evidence, but published results quite consistently demonstrate that RT using fraction dose of 2.25-2.5 Gy delivered 5 days per week up to a total dose of 52-65 Gy gives the same or even better locoregional control than standard RT.…”
Section: Discussionmentioning
confidence: 95%
“…8 Results similar to standard RT fractionation or better have been obtained with hypofractionated protocols. 3,[9][10][11][12][13] Both methods of altered fractionation have been shown to offer some advantages. Standard, accelerated, hyper-and hypofractionated regimes are used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] A study published in 2011 in International Journal of Head and Neck Surgery showed 5-year overall survival (OS) of 86%. [13] Those patients were followed for another 5 years, and here, we report our 10-year experience of treating T1 and T2 glottic carcinoma with 55 Gy in 20 fractions over a period of 4 weeks.…”
Section: Introductionmentioning
confidence: 99%